The Mechanism of Starch Over-Accumulation in Chlamydomonas reinhardtii High-Starch Mutants Identified by Comparative Transcriptome Analysis - Koo, Kwang M.; Jung, Sera; Lee, Beom S.; Kim, Jin-Baek; Jo, Yeong D.; Choi, Hong-Il; Kang, Si-Yong; Chung, Gook-H.; Jeong, Won-Joong; Ahn, Joon-Woo (Frontiers in Microbiology, 2017)
The focus of this study was the mechanism of starch accumulation in Chlamydomonas reinhardtii high-starch mutants. Three C. reinhardtii mutants showing high starch content were generated using gamma irradiation. When grown under nitrogen-deficient conditions, these mutants had more than twice as much starch than a wild-type control. The mechanism of starch over-accumulation in these mutants was studied with comparative transcriptome analysis. In all mutants, induction of phosphoglucomutase 1 (PGM1) expression was detected; PGM1 catalyzes the inter-conversion of glucose 1-phosphate and glucose 6-phosphate in both starch biosynthetic and glycolytic pathway. Interestingly, transcript levels of phosphoglucose isomerase 1 (PGI1), fructose 1,6-bisphosphate aldolase 1 and 2 (FBA1 and FBA2) were down-regulated in all mutants; PGI1, FBA1 and FBA2 act on downstream of glucose 6-phosphate conversion in glycolytic pathway. Therefore, down-regulations of PGI1, FBA1 and FBA2 may lead to accumulation of upstream metabolites, notably glucose 6-phosphate, resulting in induction of PGM1 expression through feed-forward regulation and that PGM1 overexpression caused starch over-accumulation in mutants. These results suggest that PGI1, FBA1, FBA2, and PGM1 correlate with each other in terms of coordinated transcriptional regulation and play central roles for starch over-accumulation in C. reinhardtii.